Building Customer Loyalty and Analysis Competitor in Islamic Education Institutions - Faila Sufah; Subiyantoro Subiyantoro (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine building customer loyalty and analyze competitors in Islamic Education Institutions. The research method uses a qualitative approach, namely, library research. The data analysis technique is descriptive. Building customer loyalty in Islamic educational institutions is done with several marketing strategies including establishing relationships with various components such as the community and so on, providing customer satisfaction by offering varied programs and facilities, and providing guarantees if customers are not satisfied with the services and quality that have been provided. Analysis of marketing competitors that often occur in Islamic Education Institutions includes products, marketing, prices, and cooperation networks so that they must be able to maintain quality by using various methods, one of which is creating brand awareness to create attractiveness.